Leak Detection in Medium Density Polyethylene (MDPE) Pipe Using Pressure Transient Method - Makeen, Mohd Amin; M. F., Ghazali; N. F., Adnan (IOP Publishing, 2015)
Water is an essential part of commodity for a daily life usage for an average person, from personal uses such as residential or commercial consumers to industries utilisation. Even though precaution steps have been taken, there is still having technical faulty like leaks during their transmission upon reaching the users. Ensemble Empirical Mode Decomposition Method (EEMD) with signal masking is one of the methods that implemented in this experiment by using Medium Density Polyethylene (MOPE) to analyze the position of the leakage in the pipeline. Water hammering system which the water would be abruptly shut off and that would induce an impulse throughout the pipeline, with that in turn would cause the system into a surge of water wave. The data analysis of the pressure signal that then to be decomposed into a series of wave composition with the use of EEMD signal masking method by using the matrix laboratory (MATLAB) software. The series of decomposition of signals is then carefully selected on where the supposed reflected intrinsic mode function (IMF). These IMFs that where being displayed by using a mathematical algorithm, that is known as hilbert transform (HT) spectrum. With this, the IMF signal was analyzed, and the difference of the time would be obtained and calculated. Finally, the analyzed data could be compared with the actual measurement of the leakage in term of percentage of errors.